profil kemampuan pemecahan masalah matematika siswa kelas VII-A MTs Muhammadiyah 6 Karanganyar dalam menyelesaikan soal bangun datar - Fahni, Rofik, Masduki, S.Si, M.Si (2015)
This study attempts to described profile the ability problem solving mathematics students vii-a mts muhammadiyah 6 karanganyar in resolving about wake up flat.The research is the qualitative study descriptive.The subject of study is 4 students vii-a mts muhammadiyah 6 karanganyar.The data used is a recording the interviews and test results.Methods used in this research is interview and tests.Interviews were conducted subject to two students have fulfill the KKM schools and two students not fulfill the KKM school.The research results show that students have fulfill the KKM school, in resolving problems the about wake up flat students capable of understand a problem, create a plan settlement and carry out a plan, but it check the answers back. While students who do not meet value KKM school, in resolving problems the about wake up flat less well-off students understand a problem so that wrong in deciding strategy to apply in solve the problems led on the answer are not appropriate.